rehumanize YOUR BUSINESS : How Personal Videos Accelerate Sales and Improve Customer Experience - Beute, Ethan, 1973-, author; Pacinelli, Stephen, 1977-, author (Hoboken, New Jersey : John Wiley & Sons, Inc.)
Every day, most working professionals entrust their most important messages to a form of communication that doesn't build trust, provide differentiation, or communicate clearly enough. It's easy to point to the sheer volume of emails, text messages, voicemails, and even social messaging as the problem that reduces our reply rates and diminishes our effectiveness. But the faceless nature of that communication is also to blame.